Neurological benefits of third places for young adults in healthy urban environments - Leiqing Xu; Dancheng Meng; Shin Bin Tan; Jiahua Li; Xiaolin Zhang (Frontiers of Architectural Research)
Aspects of urban environments, especially green spaces, are known to benefit mental health and well-being. However, the healing potential of urban third places remains underexamined compared to the well-documented benefits of more “natural” environments. “Third places” refers to public spaces where people gather outside of their homes (first place) and workplaces (second place), thereby supporting well-being through fostering social interaction and community engagement. Using fNIRS, Empatica E4 wristbands, questionnaires and interviews with 40 young adults in Shanghai, China, we found that third places demonstrate healing effects comparable to natural environments neurologically, psychologically, and physiologically, although they are achieved through distinct underlying mechanisms. Third places contribute to mental wellbeing through emotional pathways, primarily by fostering “pleasure” through social engagement and environmental design, while natural spaces promote “gratitude” through biophilic connections. These results underscore the importance of third places in mental health support for young adults, highlighting the need for social infrastructure interventions. Optimizing third places could create healthier, less stressful, and more emotionally positive urban environments.